THE INFLUENCE OF LEARNING INTEREST AND LEARNING MOTIVATION ON STUDENT MATHEMATICS LEARNING ACHIEVEMENT - Pebriani, Ine Theana; Purwanto, Joko; Gunawan, Gunawan; Kusuma, Jaka Wijaya (Nindikayla Institute, 2024)
Learning requires study interest and desire. Students' achievement in mathematics is influenced by their study interest and drive. This study aims to determine 1) the impact of study interest on students' mathematics learning achievement; 2) the impact of study motivation on students' mathematics learning achievement; and 3) the impact of study interest and motivation on students' mathematics learning achievement. This study was carried out in SMA Negeri 3 Banjar. Ex post facto approaches are employed in the quantitative research. This study's population was class X MIPA SMA Negeri 3 Banjar, and the sample was chosen using Cluster Random Sampling X MIPA 2. Questionnaires and tests that had passed validity and reliability assessments were employed in data collection approaches. The precondition tests are performed first, including the linearity, normalcy, multicollinearity, and heteroscedasticity tests. The correlation coefficient, coefficient of determination, partial test (t test), and simultaneous test (F test) are then used to build a multiple linear regression model. The linear regression model that was developed is Y = -13,961 + 0,581X1 + 0,663X2. According to the findings of the study, 1) interest in learning has a positive effect on students' mathematics learning achievement by 40.3%; 2) study motivation has a positive effect on students' mathematics learning achievement by 37.7%; and 3) study interest and study motivation have a significant effect on students' mathematics learning achievement by 76.4%.